Long non‐coding RNA telomerase RNA elements improve glucocorticoid‐induced osteoporosis by EZH2 to regulate DKK1. (15th February 2023) - Hu, He; Guo, Xiaodong; Mu, Tingting; Song, Huifang
Abstract: Background: Glucocorticoid‐induced osteoporosis is the most common secondary cause of osteoporosis, which increases the risk of fracture. Long non‐coding RNA telomerase RNA elements (TERC) has been proven to be closely related to osteoporosis. However, the role of TERC in glucocorticoid‐induced osteoporosis and its underlying molecular mechanism remains unclear. Methods: The in vitro model of osteoporosis was established after bone marrow mesenchymal stem cells (BMSCs) were exposed to dexamethasone (DEX). The cell viability, alkaline phosphatase (ALP) activity and mineralized nodules of BMSCs were evaluated. The messenger RNA and protein levels were detected by quantitative real‐time polymerase chain reaction and Western blot. The interaction between TERC, enhancer of zeste homolog 2 (EZH2) and dickkopf‐1 (DKK1) was confirmed by chromatin immunoprecipitation and RNA immunoprecipitation assays. Results: Bone marrow mesenchymal stem cells were isolated, identified and induced osteogenic differentiation. The findings showed that the levels of osteogenic marker genes, including ALP, Runt‐related transcription factor 2 (RUNX2) and osteocalcin (OCN) in BMSCs were increased dependent on the osteogenic induction time. Similarly, TERC was significantly increased, but DKK1 was significantly decreased during BMSC osteogenic differentiation. Functional research showed that TERC overexpression promoted cell viability, ALP activity and mineralized nodules of BMSCs and increased the levels of osteogenic differentiation‐related genes (ALP, RUNX2 and OCN), and TERC overexpression increased EZH2 protein level. Moreover, the decrease of cell viability, ALP activity and mineralized nodules induced by DEX was reversed by TERC overexpression. Furthermore, TERC inhibited DKK1 expression by promoting the histone modification of DKK1, and TERC overexpression alleviated DEX suppressed osteogenic differentiation of BMSCs by interaction with EZH2 to regulate DKK1. Conclusion: Our findings illustrated that TERC overexpression alleviated DEX‐induced osteoporosis by recruiting EZH2 to regulate DKK1. Our research provided a novel direction for the treatment of glucocorticoid‐induced osteoporosis. Abstract : TERC overexpression reduced the expression of DDK1 by regulating EZH2, thereby improving the progression of osteoporosis.